Discrimination of 13C Among Upland Rices Having Different Water Use Efficiencies - Dingkuhn, M.; Farquhar, G.D.; De Datta, S.K.; O'Toole, J.C.; Datta, SKde (Commonwealth Scientific and Industrial Research Organisation, 1991)
Discrimination of stable carbon isotopes in leaves is physiologically linked to water-use efficiency. Twenty-eight contrasting rice (Oryza sativa L.) cultivars were grown in the Philippines as upland rice under continuous, mild water stress. In situ measurements of leaf level water-use efficiency (WUE), net photosynthesis, conductance, water potential and leaf rolling were reported previously. The present study used leaf samples from the same experiment to determine, by means of a mass spectrometer, the carbon isotope discrimination (-) and total C and N content. Among rice cultivars, - ranged from 19.8 to 21.5960, with japonica types having the lowest mean -, aus types, the greatest, and indica types, intermediate-the opposite pattern to that observed for WUE. Carbon isotope discrimination was negatively correlated with WUE across all cultivars (P < 0.001) and within japonica (P < 0 -01) and aus (P < 0.05) groups, but not among indica rices. No correlation was observed between - and any other measured variable. Varietal differences in - and WUE were not related to leaf N content or stomata1 conductance. High WUE was associated with high leaf C content (P < 0.01), with aus cultivars having the lowest mean WUE and C content among the genetic groups. We conclude that even under variable field conditions, analysis of foliar - is a potential tool to identify water-use efficient rice genotypes.